The Influence of Product Quality on The Purchase Decision of Wardah Cosmetics in Karawang City - Mutiara Ramadhani Putri Jangkung; Ajat Sudrajat (Fakultas Bisnis, 2022)
The purpose of this study was to determine the effect of product quality and price on purchasing decisions for wardah products in the city of karawang, this research method used quantitative methods with descriptive and verification approaches. The population used in this study is using social media followers Instagram Wrdah Beauty as much as 2,900,000 with 100 samples used. The validity of the data used is the validity and reliability test and the classical assumption test using linearity, normality, homoscedasticity, non-autocorrelation, and multicollinearity tests. The data analysis technique used is a simple regression analysis technique with partial and simultaneous hypothesis testing. The results of this study are there is a positive and significant influence on the quality of product to purchasing decisions.